The hermit crab - Goodrich, Carter (New York : Simon & Schuster Books for Young Readers, 2009)
Absorbed in his search for food, a shy hermit crab, disguised in a fancy new shell, inadvertently rescues a flounder caught beneath a trap and wins the admiration of the other marine animals.
A Junior Library Guild selection
Ages 6-10.
Keywords: Hermit crabs -- Juvenile fiction; Crabs -- Juvenile fiction; Marine animals -- Juvenile fiction; Hermit crabs -- Fiction; Crabs -- Fiction; Marine animals -- Fiction; Humorous stories